A 2D/2D S-scheme photo-Fenton catalyst based on ultrathin Bi2MoO6 and Fe2O3 hexagonal nanosheets for efficient tetracycline degradation. Issue 8 (8th March 2021) - Wang, Wenliang; Zhao, Wenli; Huang, Huimin; Chen, Ruyao; Shi, Haifeng
Abstract : Fe2 O3 /Bi2 MoO6 heterojunctions exhibit an observably improved photo-Fenton catalytic tetracycline degradation activity, which is accredited to an 2D/2D S-scheme charge transfer mechanism. Abstract : In order to solve the increasingly serious environmental pollution and energy crisis as soon as possible, engineering of two-dimensional/two-dimensional (2D/2D) S-scheme heterojunctions is in the spotlight. Herein, two-dimensional/two-dimensional (2D/2D) S-scheme Fe2 O3 /Bi2 MoO6 was designed and fabricated through a facile hydrothermal strategy, which constructed an advanced photocatalytic-Fenton coupling system. With the assistance of a low concentration of H2 O2, the 2D/2D Fe2 O3 /Bi2 MoO6 with an Fe2 O3 weight ratio of 0.5% displayed significantly enhanced photo-Fenton catalytic activity toward tetracycline, which was 3.2 and 2.0 times that of Fe2 O3 and Bi2 MoO6, respectively. The markedly enhanced photo-Fenton catalytic activity was attributed to the large surface area and efficient charge transfer of 2D/2D S-scheme Fe2 O3 /Bi2 MoO6, as well as the photo-Fenton system constructed by H2 O2 and continuous Fe 3+ /Fe 2+ conversion under visible light irradiation. According to the active species trapping experiments and photoluminescence spectra, a novel 2D/2D S-scheme charge transfer mechanism of Fe2 O3 /Bi2 MoO6 was reasonably proposed. Fe2 O3 /Bi2 MoO6 composites displayed a broad application prospect due to their recyclability demonstrated by the cycling experiments. This work provides strong evidence that 2D/2D S-scheme Fe2 O3 /Bi2 MoO6 heterostructures are promising candidates for the photo-Fenton treatment of antibiotics.